Proximal Femoral Fracture in Hip Arthrodesis Treated with Double Reconstruction Plates - Shunsuke Asakawa; Takeo Mammoto; Atsushi Hirano (Case Reports in Orthopedics)
We present a rare clinical case of a 90-year-old female who sustained a proximal femoral neck fracture following long-standing hip arthrodesis. Since the fracture occurred relatively proximally and involved the pelvis, double-plate fixation was chosen to achieve rigid fixation. The reconstruction plate was placed at the posterior and anterior columns individually through single vertical incision. She was treated successfully, and she attained preinjury activity level. Proximal femoral fractures in arthrodesed hips need to be recognized as a fracture between the pelvis and femur. Rotational stress from the trunk and lower extremity requires rigid fixation to minimize the increase of displacement and the risk for nonunion.